1995
DOI: 10.1139/x95-207
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variation and parameter estimates in Taxusbrevifolia (Pacific yew)

Abstract: Pacific yew (Taxusbrevifolia Nutt.) is a shade-tolerant gymnosperm native to the western United States and Canada. It recently gained attention as the source of Taxol® (paclitaxel), a promising new anticancer drug. Large-scale harvest of mature Pacific yew trees for the extraction of paclitaxel has resulted in the need for improved forest management practices and an increased understanding of the amount and distribution of genetic variation in the species. We partitioned estimates of genetic variance for alloz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
1

Year Published

1999
1999
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 0 publications
1
10
1
Order By: Relevance
“…RAPD data are, however, in contrast to molecular studies on other woody perennials sampled across a similar geographic scale, which generally indicate relatively little variation among populations for nuclear-encoded molecular markers (e.g., Leonardi and Menozzi, 1995;Wheeler et al, 1995;Zanetto and Kremer, 1995;Bodénès et al, 1997; for reviews, see Hamrick et al, 1992;Hamrick and Godt, 1989;Nybom and Bartish, 2000).…”
Section: Partitioning and Levels Of Genetic Variation In Sesbaniamentioning
confidence: 87%
“…RAPD data are, however, in contrast to molecular studies on other woody perennials sampled across a similar geographic scale, which generally indicate relatively little variation among populations for nuclear-encoded molecular markers (e.g., Leonardi and Menozzi, 1995;Wheeler et al, 1995;Zanetto and Kremer, 1995;Bodénès et al, 1997; for reviews, see Hamrick et al, 1992;Hamrick and Godt, 1989;Nybom and Bartish, 2000).…”
Section: Partitioning and Levels Of Genetic Variation In Sesbaniamentioning
confidence: 87%
“…1996), populations of T. wallichiana seem to maintain large differentiation values between populations, probably because of its habitat as part of the undergrowth in forests. There, wind velocities are greatly reduced and the temperature inversions negatively affect pollen dispersal (Tauber 1967; Levin & Kerster 1974; Wheeler et al . 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Despite its dioecy, wind-pollination and endozoochorous seed dispersal (DiFazio 1996;Wilson et al 1996), populations of T. wallichiana seem to maintain large differentiation values between populations, probably because of its habitat as part of the undergrowth in forests. There, wind velocities are greatly reduced and the temperature inversions negatively affect pollen dispersal (Tauber 1967;Levin & Kerster 1974;Wheeler et al 1995). The significant population structuring and high population differentiation recorded for T. wallichiana would fit a very limited range of wind-mediated pollen flow, as indicated earlier for Taxus by Allison (1990) who reported that the efficiency of dispersal of T. canadensis pollen drops significantly after a few metres under natural conditions, this is despite the small size of Taxus pollen (17-21.5 µm, Xing et al 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Since the 1980s, abundant allozyme studies of widespread, open-pollinated, coniferous species in the western United States and elsewhere-most of which have wind-dispersed seed-s-have composed a rather consistent pattern of genetic architecture for this taxonomic group (e.g., Dancik and Yeh 1983;Hiebert and Hamrick 1983;Li and Adams 1989;Wheeler et al 1995). For such species, genetic differences among populations are low and within populations are high (e.g., Hamrick and Godt 1990).…”
Section: Genetic Structure In Relation To Other Western Conifersmentioning
confidence: 99%